Sexual differences in morphology and winter diet of the Eurasian magpie (Pica pica) in Hungary - Imeri, Miranda; Katona, Krisztián (COLUMELLA – Journal of Agricultural and Environmental Sciences, 2022)
Eurasian magpie (Pica pica) is a widely distributed, common species of the Corvidae family. Since magpies have lived close to humans for centuries, we have much information about the species. However, there are few data about morphological and dietary differences between sexes, primarily due to their monomorphic and omnivorous, and opportunistic characteristics. The aim of the study was to analyse the sexual differences in the morphological characteristics, simultaneously provide the body measurements for both sexes with a high level of accuracy and determine the diet composition through stomach content analysis during the winter. The samples were taken from hunting in February of 2020, in Hungary. The linear measurements of body parts (eight variables considered) have been done for all individuals (n=30), and the values were compared between the sexes. The stomach contents were categorized among five main food components, and comparisons of stomach contents and their weights were also performed between males and females. The results concluded that there were no significant differences between the sexes in the studied morphological variables. The dietary analysis revealed that during the winter magpies fed on a range of different food types, with seeds, invertebrates, and vertebrates being the most frequently consumed food. We revealed slight differences between sexes in the consumption of the two latter categories. Our investigations supported earlier findings on the high morphological and dietary similarities of the two sexes also in case of a Hungarian magpie population. These results can serve as a potential basis for further research on magpies in Europe.
Keywords: body measurements, monomorphic birds, food composition, stomach analysis, Corvidae